MAKNA SIMBOLIK ULOS DALAM PERNIKAHAN ADAT ISTIADAT BATAK TOBA DI BAKARA KECAMATAN BAKTIRAJA KABUPATEN HUMBANG HASUNDUTAN PROVINSI SUMATERA UTARA - Yondhi Darmawan; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Marriage is one of the processes through which the life of every person. Marriage is considered to be holy and sacred procession because it is only done once in a lifetime, as well as by the Toba Batak society. Marriage by Batak Toba became a symbol of joy and pride. In undergoing the wedding procession will not be separated from the prevailing mores. In wedding customs Batak Toba Ulos becomes very important and can not be missed. Ulos is a type of clothing-shaped piece of cloth that is considered kemarat by Toba Batak society. Ulos became a symbol of strength and is considered to provide warmth for sipenggunanya. Bakara is one of the places of origin Batak Toba originated. Bakara society still holds tightly to maintaining the prevailing customs, as well as the use of Ulos both in weddings and events are also other customs. . The purpose of this study was to look for the symbolic meaning Ulos examined physically and socially.This research used qualitative research methods. Subject or resources that study consisted of 9 people, 2 Raja Hata, 4 people from different professions and 3 persons through purposive technique. Techniques in this study using observation, interviews, and documentation.Results of research conducted by the authors is that the symbolic meaning Ulos in customs Batak Toba can be assessed through two aspects: the physical and social aspects. The physical aspect of all things related to the real form Ulos such as color, and size. In Ulos color can be seen from the three basic colors of red, white, and black. The red color symbolizes strength and leadership, white color symbolizes purity and compassion, and the black color symbolizes the blood, breath, and warmth. By size Ulos has a length of 1.8 meters, a width of 1 meter and the size Ulos may not be altered in order to make meaning of Ulos will never change. In terms of the social aspect that everything Something series of governance-related events such as dancing (manortor), Delivery of carp (Deke), until the procession Ulos giving and receiving Ulos (mangulosi), however the most important social meaning is submission of sacred words (hatana) shortly before mangulosi done. All of the purposes when procession have gread meaning like symbol of joy, symbol of love, symbol of rewards.Key Words : Symbolic, Ulos, marriage customs, Batak Toba, Bakara